LEKSIKON NAMA ORANG PADA ETNIS MIYAH: KAJIAN EKOLINGUISTIK - Yosefina Baru (Balai Bahasa Provinsi Papua, 2019)
This research oriented ecolinguistic study aimed to assess or inventory lexicons of the physical environment/physical and social environment that is used as the name of the ethnic Miyah. This research is preliminary only aims to describe or description what kind of closeness or intimacy between ethnic Miyah to the physical environment/physical and social environment through the lexicon associated with the name of the place, the name of the condition of the physical/geographical name of flora and fauna found in the environment Miyah ethnic community life, as well as the name of cultural objects and names associated with key events/conditions associated with the birth of a person who is selected and used as the name of the person on ethnic Miyah.